Islamisasi Nusantara dan Sejarah Sosial Pendidikan Islam - Alfiani, M. Miftah; Suweleh, Samiha; Jannah, Lilis Kholifatul; Mahfud, Choirul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
The process of entering Islam in Indonesia and to do with the development of Islamic education in the days before the arrival of Islam. The role of the muballigh and trader from Saudi who make trade relations with the Indonesian people really help the process of the entry of Islam in Indonesia. Apart from trade then followed up by the religious teacher and sufi travelers. The history of Islamic education had come to very pertaining to Islamic history so there is period history among them a period of classic, Islamic education a middle period and modern period. The process of Islamic education at first goes on not just limited to one place and time it, but wherever and whenever when there was contact between muballigh, merchants and natives, then at that moment also was also conducted. Islamic education system at first raged on in a family environment, but is expanding in surau, the mosque, and eventually go on home the nobles.